Clinico-Radiological Correlation in 7 Cases of Airway Compression by Vascular Anomalies on MDCT - Yadav, Anurag; Buxi, TBS; Reddy, Supraja; Singh Ghuman, Samarjit; Rawat, Kishan Singh; Jayamma, Savitha Srirama (Global Journal of Medical and Clinical Case Reports, 2015)
<span style="color: #222222; font-family: Roboto, serif; font-size: 15px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Compression of the airway by vascular anomalies is a co-morbidity occurring frequently in children with congenital heart diseases. Here we presented a cohort of 7 patients with respiratory distress who showed airway compression due to vascular anomalies on evaluated with multidetector computed tompgraphy. The anomalies detected were double aortic arch, left sided aortic arch with aberrant right subclavian artery, right sided aortic arch with aberrant left subclavian artery, left pulmonary artery forming a pulmonary sling and dilated right pulmonary artery compressing the right main bronchus.